Cardioprotective effects of sitagliptin against doxorubicin-induced cardiotoxicity in rats - El-Agamy, Dina S (Exp Biol Med (Maywood), 2016)
There is a large body of evidence suggesting that inhibitors of dipeptidyl peptidase-4, such as sitagliptin, may exhibit beneficial effects against different inflammatory disorders. This investigation was conducted to elucidate the potential ability of sitagliptin to counteract the injurious effects of doxorubicin in cardiac tissue. Male Wistar rats were pretreated with sitagliptin for 10 days then treated with a single dose of doxorubicin (20 mg/kg, i.p). Electrocardiography, biochemical estimation of serum and tissue markers, and histo- and immunopathological examinations were done. Results have shown that supplementation with sitagliptin resulted in significant improvement of cardiac function with contaminant decrease in serum markers of doxorubicin-induced cardiotoxicity. These results were supported by the histopathological results. Furthermore, a marked protection against oxidative stress was evident through reduction of lipid peroxidation and prevention of reduced glutathione content depletion and superoxide dismutase activity reduction in cardiac tissue of rats pretreated with sitagliptin in combination with doxorubicin. Moreover, sitagliptin ameliorated the activation of nuclear factor kappa-B and the release of inflammatory cytokines, tumour necrosis factor-alpha and nitric oxide. Finally, sitagliptin attenuated doxorubicin-induced increase in the expression of pro-apoptotic protein Bax and in the apoptotic marker, caspase-3. Collectively, these data indicate that sitagliptin pretreatment could alleviate doxorubicin-induced cardiotoxicity via reducing oxidative damage and its subsequent inflammation and apoptosis.